PENERAPAN MOTION GRAPHIC PADA IKLAN LAYANAN MASYARAKAT “DUA FAKTA” - Astuti, Aprilina Dwi (Cinelook: Journal of Film, Television, and New Media, 2024)
Public Service Advertisements (PSAs) are the process of conveying information, which is persuasive and educational in nature. For this reason, the packaging of PSAs needs to be packaged carefully in order to produce work that is easily understood by the audience.  One way to package PSAs to produce interesting and easy-to-understand impressions needs to be packaged using motion graphics. The aim of this research is to apply motion graphics to the production of the public service advertisement "Two Facts". This research uses a qualitative descriptive method, the research process goes through three stages, namely pre-production, production and post-production. The results of this research show that the applied motion graphics can create impressions that are easy to understand depending on the planning process, selection and application of motion graphics techniques that are in accordance with the specified objectives. In this work, 2D compositing and flat animation techniques are applied combined with cutting by narration image continuity techniques.